LUMO's modulation by electron withdrawing unit modification in amorphous TAT dumbbell-shaped molecules1. Issue 12 (28th March 2015) - Bulut, Ibrahim; Lévêque, Patrick; Heinrich, Benoît; Heiser, Thomas; Bechara, Rony; Zimmermann, Nicolas; Méry, Stéphane; Ziessel, Raymond; Leclerc, Nicolas
<x xml:space="preserve">Abstract</x> Investigation of triazatruxene-based dumbbell-shaped amorphous molecules in which chemical design allows to tune the optoelectronic properties of the donor molecule without changing significantly its morphological behaviour.